Ketaatan Pelaporan Kapal pada Stasiun Radio Pantai bagi Keselamatan Pelayaran dalam Perspektif Sosiologi Hukum (Studi Kasus di Kantor Distrik Navigasi Kupang) - Boni, Arianto Baki; Atang, Ahmad; Laan, Rahmat; Darajad, Syarifuddin; Beni, Wahid Hasyim TRA (Universitas Hamzanwadi, 2026)
Maritime safety is a crucial aspect of sea transportation that requires effective coordination and communication between vessels and coastal authorities. One of the key instruments in ensuring maritime safety is the routine reporting of vessels to Coastal Radio Stations (CRS). This study aims to analyze the level of vessel compliance in reporting to the CRS and its implications for maritime safety. The research employs a qualitative descriptive approach, with data collected through observation, interviews with CRS officers and ship crew members, and documentation of vessel reporting records. The findings indicate that the level of reporting compliance varies and is influenced by factors such as regulatory awareness, the technical condition of communication equipment, and the safety awareness of ship crews. Insufficient reporting may hinder monitoring processes and delay rapid response to maritime incidents. This study recommends enhanced dissemination of relevant regulations, stricter supervision, and improvements in communication infrastructure as measures to increase reporting compliance and ultimately improve maritime safety.